2023
DOI: 10.7227/jha.091
|View full text |Cite
|
Sign up to set email alerts
|

Refugees in the Digital Economy

Abstract: The current scale and duration of displacement prompts renewed urgency about livelihoods prospects for displaced people and the role of humanitarian organisations in fostering them. This special issue focuses on how aid organisations, together with the private sector and other actors, have worked to include refugees in new forms of online work within the web-based digital economy. Building on comparative analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Their findings point to the need for a more inclusive approach to humanitarian interventions during urban displacement crises. These studies call for more nuanced, inclusive refugee policymaking and intervention design strategies [27].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings point to the need for a more inclusive approach to humanitarian interventions during urban displacement crises. These studies call for more nuanced, inclusive refugee policymaking and intervention design strategies [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This echoes the study wherein Syrian refugees demonstrated a positive attitude towards blended learning, a transformative approach to achieving academic objectives. Additionally, the research underlines the importance of crafting interventions specific to refugees' needs and demographic profiles, an approach also advocated by the authors of [27] in addressing urban displacement crises. This study identifies challenges that could hinder specific interventions and proposes potential solutions that can lead to a more efficient and effective implementation, ultimately maximizing their impact in achieving zero hunger.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%